The effectiveness of hyperbaric oxygen therapy for managing radiation-induced proctitis – results of a 10-year retrospective cohort study - Moreira Monteiro, António (2023)
Funding Information: We thank Professor Elisabete Fernandes from the Faculdade de Medicina (Universidade de Lisboa) for collaborating on the statistical analysis. We also thank all the staff of the Centro de Medicina Subaquática e Hiperbárica (Armed Forces Hospital, Lisbon) for facilitating the consultation of the archived medical records. Publisher Copyright: Copyright © 2023 Moreira Monteiro, Alpuim Costa, Mareco and Espiney Amaro.